Understanding household health through data linkage. - Mai Stafford; Sarah Deeny; Kathryn Marszalek; Jenny Shand (International Journal of Population Data Science, 2022)
Objectives Household factors can affect the level and type of health and social care a person with long-term conditions needs. Information on household composition and health needs within households is not easily available in routine health records but linked data from health providers and local government can address this gap.